Legal Responsibilities Of Notaries In The Preparation Of Sale And Purchase Deed Related To Fisheries Crimes - Moertiono, R Juli; Lubis, M Syukran Yamin; Sugesti, Tutik (Faculty of Law, Universitas Pekalongan, 2024)
The legal responsibility of notaries in making sale and purchase deeds related to fisheries crimes. Fisheries crimes, such as illegal fishing, have a significant impact on marine ecosystems and the national economy. In practice, notaries are often involved in the preparation of deeds of sale and purchase agreements that may be related to the proceeds of the crime. This study uses a normative juridical method with a legislative approach and case studies to evaluate aspects of notary legal responsibility. The results of the study show that notaries have a legal obligation to ensure the legality of the object of the transaction, and can be held accountable if they are negligent in carrying out these duties